2019
DOI: 10.1016/j.scitotenv.2019.133888
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient criteria for surface waters under the European Water Framework Directive: Current state-of-the-art, challenges and future outlook

Abstract: The aim of European water policy is to achieve good ecological status in all rivers, lakes, coastal and transitional waters by 2027. Currently, more than half of water bodies are in a degraded condition and nutrient enrichment is one of the main culprits. Therefore, there is a pressing need to establish reliable and comparable nutrient criteria that are consistent with good ecological status.This paper highlights the wide range of nutrient criteria currently in use by Member States of the European Union to sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(97 citation statements)
references
References 68 publications
2
77
0
2
Order By: Relevance
“…However, despite numerous policy directives and conventions, the most recent assessment of trophic status of European coastal ecosystems (European Environmental Agency [EEA], 2018) shows that 40% of coastal (continental shelf) waters and 66% of transitional waters (estuaries) failed to achieve the objective of good ecological status 34 (Poikane et al, 2019). Therefore, a new Fertilizing Products Regulation was adopted in 2019, and 32 The practice of tilling sloped land along lines of consistent elevation in order to conserve rainwater and to reduce soil losses from surface erosion.…”
Section: Europementioning
confidence: 99%
“…However, despite numerous policy directives and conventions, the most recent assessment of trophic status of European coastal ecosystems (European Environmental Agency [EEA], 2018) shows that 40% of coastal (continental shelf) waters and 66% of transitional waters (estuaries) failed to achieve the objective of good ecological status 34 (Poikane et al, 2019). Therefore, a new Fertilizing Products Regulation was adopted in 2019, and 32 The practice of tilling sloped land along lines of consistent elevation in order to conserve rainwater and to reduce soil losses from surface erosion.…”
Section: Europementioning
confidence: 99%
“…A Policy Forum Review in Science concluded that amelioration of the negative impacts of nutrient enrichment should be made by control and reduction of both N and P (Conley et al 2009); more recent work supports this contention (Lewis et al 2011, Wurtsbaugh et al 2019. Recent considerations on the Water Framework Directive (Poikane et al 2019) also recognise the importance of considering N as well as P reduction. Although seemingly counterintuitive, sites failing P targets (high P) might be most effectively managed by reducing N, evidenced by our finding that the phytoplankton are most likely to be N limited, and those failing N targets (high N) may be best managed by reducing P, evidenced by our finding that the phytoplankton are most likely to be P limited.…”
Section: Implications Of Nutrient Limitation Status and Managementmentioning
confidence: 99%
“…Harmonisation of Nordic methods, including nationally established RCs for nutrients, will be required to compare impacts of the land use changes across countries. As noted by Poikane et al (2019), the G/M boundaries for European rivers vary widely among the EU countries, implying variations in the associated RC levels as well.…”
Section: Introductionmentioning
confidence: 97%